1996
DOI: 10.1177/001088049603700427
|View full text |Cite
|
Sign up to set email alerts
|

Property-Management Competencies for Management Trainees

Abstract: The most important property-management skills for management trainees to learn involve knowing how to work with people, rather than technical matters. In a survey, 107 hotel managers rated the importance of 18 property-management competencies for management trainees. The 18 competencies were drawn by an expert panel from a comprehensive list of 72 possible competencies. The most important of the 18 were interacting smoothly with a wide variety of people and operating effectively under pressure. Technical matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 8 publications
3
42
0
Order By: Relevance
“…Consistent with past findings, respondents attribute management success to such intrinsic attributes as having internal locus of control (Brownell, 1994), as well as pursuing self-development, long-term career goals (Ludkin and Juwaheer, 2000) and willingness to make personal sacrifices (Brownell, 1994). Also dating back in the hospitality literature as early as 1988, personal merits and abilities such as possessing professional appearance and poise, practicing good work ethics and having good communication skills have been well established and documented as important management requisites (Tas, 1988;Okeiyi et al, 1994;Tas et al, 1996;Kay and Russette, 2000;Perdue et al, 2000). The importance ratings of these attributes by respondents in this study are consistent with past findings.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with past findings, respondents attribute management success to such intrinsic attributes as having internal locus of control (Brownell, 1994), as well as pursuing self-development, long-term career goals (Ludkin and Juwaheer, 2000) and willingness to make personal sacrifices (Brownell, 1994). Also dating back in the hospitality literature as early as 1988, personal merits and abilities such as possessing professional appearance and poise, practicing good work ethics and having good communication skills have been well established and documented as important management requisites (Tas, 1988;Okeiyi et al, 1994;Tas et al, 1996;Kay and Russette, 2000;Perdue et al, 2000). The importance ratings of these attributes by respondents in this study are consistent with past findings.…”
Section: Discussionsupporting
confidence: 67%
“…Numerous authors have identified KSAs in leadership as an important element of managerial success, as well (Tas, 1988;Okeiyi et al, 1994;Tas et al, 1996;Kay and Russette, 2000). In a study to assess skills needed by tourism managers, respondents stated that the most important managerial skills are leadership followed by interpersonal communications and employee relations (Breiter and Clements, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This competency cluster was identified as important for tourism managers (Breiter and Clements, 1996), recent hotel graduates working as management trainees (Tas et al, 1996), catering managers (Wilson et al, 2000), and hotel managers (Christou, 2002), to name a few.…”
Section: Article In Pressmentioning
confidence: 99%
“…Little in the way of service-related behaviors are provided. Tas et al (1996) Property Management Trainee Competencies Eighteen behaviors were evaluated by hotel general managers. A single general behavior item is included which mentions customers and was listed as "Interacts smoothly with a wide variety of people-e.g., customers, staff, contractors."…”
Section: Author(s)mentioning
confidence: 99%
“…While the two were considered "essential" and received both the first and fourth highest mean scores, they represent only a small part of the model. In a later study, Tas et al (1996) looked at competencies for property-management. Again, a service-related competency was at the top of the list; however, the emphasis of the competency was "interacting with a wide variety of people," which included "staff and contractors" as well as "customers."…”
Section: Introductionmentioning
confidence: 99%